Hydraulic Performance Evaluation of Water Conveyance System of Wonji Shoa Irrigation Scheme in Ethiopia - Aschenaki, Mekonnnen (ASTU, 2024)
Water Is A Crucial Global Resource, Used By Living Things For Survival And In Various Industrial Processes. The Water Losses In Canals Have A Significant And Diverse Effect On The Efficient Water Supply To Fields As It Is A Basic Element Of Irrigation Systems. A Complex Web Of Interconnected Hydrologic And Hydraulic Barriers Limits The Wonji Shoa Irrigation Scheme's Conveyance Efficiency. The Serious Problem In The Domain/Field Of Irrigation Systems Is Addressing Water Conveyance Inefficient And Minimizing Canal Water Loss. One Of The Major Challenges In The Wonji Shoa Irrigation Scheme Is Bridging The Accelerated Gap Between The Required And Available Water And Pinpoint Areas That Need Management Intervention To Increase The Conveyance System's Efficiency. The Aim Of This Research Is To Evaluate Hydraulic And Hydrologic Parameters In Irrigation Conveyance Systems, Thereby Enhancing Transportation Efficiency And Aiding The Identification Of Areas Of Water Loss. The Various Methods Used To Assess The Impact Of Hydraulic And Hydrologic Parameters On Conveyance Efficiency In Irrigation Canals, Include Field Measurements, The Velocity Area Method, Minitab Software For Statistical Analysis, Cropwat 8.0 For Estimation Of Evaporation Loss And Inflow Outflow, And Empirical Methods To Calculate Seepage Loss. In This Study, The Overall Conveyance Efficiency Is 40.29% And 31.59% In The Right And Left Branches Of The Whole Conveyance System, Respectively, And On Average 35.94%. Most Of The Canals Are Earthen; Considerable Water Is Lost Due To Seepage, Except In The Lined Main Canal, Where There Is Minimum Loss. Among The Hydraulic Parameters Analyzed, Water Depth (Wd) And Wetted Perimeter (Pw) Emerge As The Predominant Factors. The Comparison Of Empirical Formulas With Field Observations (Inflow-Outflow) For The Purpose Of Quantifying Seepage Loss Within Hydrologic Factors Yields Significant Insights Regarding The Precision And Reliability Of Various Estimation Techniques. The Results Obtained From The Inflow-Outflow Method Emphasize The Crucial Relevance Of In-Situ Measurements And Real Time Data Capture For More Accurate Evaluations, Even Though Empirical Formulas Provide A Quick And Easily Accessible Route To Estimation. The Overall Seepage Loss Was 25.7%, And For Lined Main Canals It Was 0.016%/100 M, And The Unlined (Earthen) Result Was 1.16%/100 M, And Evaporation Loss Is Quite Low Implies Neglected,. Overall, Optimizing Canal Designs To Minimize Wetted Perimeter And Controlling Water Depth Has Been Crucial For Reducing Seepage Loss And Enhancing Conveyance Efficiency. Seepage Loss Is The Prime Factor In Water Loss In Most Of The Earthen (Unlined) Canals.
Hydraulic Performance Evaluation Of Water Conveyance System Of Wonji Shoa Irrigation Scheme In Ethiopia
Keywords: Conveyance efficiency, hydraulic parameter, hydrologic parameter, seepage loss, and Water scarcity; Conveyance Efficiency, Hydraulic Parameter, Hydrologic Parameter, Seepage Loss, And Water Scarcity